2020
DOI: 10.1021/acs.iecr.0c04586
|View full text |Cite
|
Sign up to set email alerts
|

Novel Polyurethane Elastomer Modified by Hybrid Shell Nano-/Microcapsules for Unique Self-Lubricating Behavior

Abstract: Self-lubricating microcapsules containing liquid paraffin as the core material were successfully synthesized with polyurethane (PU)/silica (SiO2) as the hybrid shell material using a sol–gel process and an interfacial polymerization method. The self-lubricating microcapsules were adopted as the filling matrix, which was compounded with the PU elastomer through an in situ polymerization method to improve the self-lubricity of the PU elastomer. The self-lubricating properties of the PU composites with different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
(47 reference statements)
0
12
0
Order By: Relevance
“…In addition, the peak at 7.86 ppm related to the hydrogen protons of CH═N is observed. 18 Meanwhile, in the 13 C NMR spectroscopy of the PA diol (Figure S3), the peaks at 144 ppm (C═N), 126 ppm (C C of benzene ring) and 167 ppm (C═O) could be found, respectively. These results indicated that PA diol had been successfully synthesized.…”
Section: Structure Of Pa and Wpu-pa-xmentioning
confidence: 98%
See 4 more Smart Citations
“…In addition, the peak at 7.86 ppm related to the hydrogen protons of CH═N is observed. 18 Meanwhile, in the 13 C NMR spectroscopy of the PA diol (Figure S3), the peaks at 144 ppm (C═N), 126 ppm (C C of benzene ring) and 167 ppm (C═O) could be found, respectively. These results indicated that PA diol had been successfully synthesized.…”
Section: Structure Of Pa and Wpu-pa-xmentioning
confidence: 98%
“…The 1 H NMR and 13 C NMR spectra were acquired on a German-Swiss Bruker DRX-400 superconducting 1 H NMR and 13 C NMR spectrometer with d 6 -DMSO as the solvent at 25 C. Element content was determinate by element tester (elementar varioel cube).…”
Section: Characterizations Of Wpu-pa-xmentioning
confidence: 99%
See 3 more Smart Citations